Tourism pressures and depopulation in Cannaregio: Effects of mass tourism on Venetian cultural heritage. Issue 2 (15th May 2017) - Zanini, Sara
Abstract : Purpose: The purpose of this paper is to understand the effects of mass tourism on urban communities in the historic centre of Venice, Italy. Through a survey in Cannaregio district, it explores the correlation between tourism pressures and the depopulation phenomenon and its mechanisms, the agents involved and the effects of depopulation on local life. Design/methodology/approach: Semi-structured interviews with local residents, international experts and municipality officers, together with an analysis of literature on the topic allowed the collection of original qualitative data. Findings: Venice is a popular tourist destination which risks being overwhelmed by its own success. Aside from environmental and structural issues, the city is experiencing socio-economic changes, such as the depopulation of its historic centre. The paper suggests that both direct and indirect relationships exist between tourism pressures and depopulation in Venice. The findings point to a need to develop strategies and manage tourism efficiently, and to promote diversification of local business in the interests of reducing tourism-induced demographic changes and improving local residents' quality of life. Practical implications: The outcomes of this study will be useful for local residents and heritage managers in understanding the mechanisms behind tourism mismanagement and the phenomenon of depopulation. Such heightened understanding will be useful in encouraging future cooperation between stakeholders and highlighting the key role that local residents play. Originality/value: The study analyses tourism pressures and depopulation using qualitative data, focussing not only on the people-related aspect with its loss of intangible practices, but also on the property-related aspects of tourism and their effects on the local real estate market.